Visualization technology-based construction safety management: A review - Guo, Hongling; Yu, Yantao; Skitmore, Martin (Automation in construction, 2017)
Construction safety management has been a popular issue in research and practice in recent years due to the high accident and death rates in the construction industry. The complexity and variability of construction sites makes safety management more difficult to implement than in other industries. As a promising technology, visualization has been extensively explored to aid construction safety management. However, a comprehensive critical review of the visualization technology in construction safety management is absent in the literature. This paper provides a comprehensive review to investigate research and development, application methods, achievements and barriers to the use of visualization technology in safety management, and suggests possible future research directions to extend its application. It is found that visualization technology can improve safety management by aiding safety training, job hazard area (JHA) identification and on-site safety monitoring and warnings, but there are barriers or limitations involved. Existing location technologies, for instance, can perform well only in relatively small areas due to their generally poor penetrating performance. Finally, possible future research directions are proposed to benefit the extensive application of visualization technology for construction safety management in both theory and practice. •The achievements and barriers of VT in construction safety management are reviewed.•The review is organized according to construction management periods and subjects.•78 relevant research papers from 2000 to 2015 are reviewed.•Possible future research directions of VT are proposed to extend its application.